FT-IR, UV AND ANTIMICROBIAL ACTIVITY WITH ANIA SOMNIFERA AND WITHANIA OBTUSIFOLIA - A. RAMACHANDRAN; M. SENTHIL KUMAR (International Journal of Pharma and Bio Sciences, 2014)
The present study was to compare the Phytochemical and Antimicrobial analysis of W. somnifera and W. obtusifolia. In the Ethanolic leaf and root extract of Withania species were screened for phytochemical compounds by qualitative and FT-IR, UV method. Withania species have been used for remedies of human pathogen because they contain therapeutic compounds. This research work was mainly focused to indicate on the identification of electron transition and the functional group of phytochemical constitute like wise FT-IR and UV spectroscopy.